The Potential Role of Probiotics in the Management of Childhood Autism Spectrum Disorders - J. William Critchfield; Saskia van Hemert; Michael Ash; Linda Mulder; Paul Ashwood (Gastroenterology Research and Practice)
Gastrointestinal (GI) dysfunction has been reported in a substantial number of children with autism spectrum disorders (ASD). Activation of the mucosal immune response and the presence of abnormal gut microbiota are repeatedly observed in these children. In children with ASD, the presence of GI dysfunction is often associated with increased irritability, tantrums, aggressive behaviour, and sleep disturbances. Moreover, modulating gut bacteria with short-term antibiotic treatment can lead to temporary improvement in behavioral symptoms in some individuals with ASD. Probiotics can influence microbiota composition and intestinal barrier function and alter mucosal immune responses. The administration of probiotic bacteria to address changes in the microbiota might, therefore, be a useful novel therapeutic tool with which to restore normal gut microbiota, reduce inflammation, restore epithelial barrier function, and potentially ameliorate behavioural symptoms associated with some children with ASD. In this review of the literature, support emerges for the clinical testing of probiotics in ASD, especially in the context of addressing GI symptoms.